Flat circle bundles, pullbacks, and the circle made discrete - John Oprea; Daniel Tanré (International Journal of Mathematics and Mathematical Sciences)
We use basic homotopical methods applied to Lie groups made discrete to prove that the real Euler class of a circle bundle vanishes if and only if the bundle is flat.